(The Effect of Ascorbic Acid and Sodium Erythorbate on Processing of Kolang-Kaling (Arenga pinnata Merr) in Syrup - Dwi Sutrsiniati; Harry Wiriano (Warta Industri Hasil Pertanian, 1989)
Antioxidant were added to the processing of "kolang-kaling" (Arenga pinnata Merr) in syrup processing as ascorbic acid, sodium erythorbate, a mixture of ascorbic acid and sodium erythorbate. The products were stored at room temperature of three months. Total soluble solid, pH, vitamin c, total bacterial count and organoleptic test were observed during storage. The addition of ascorbic acid or ascorbic acid and sodium erythorbate resulted in decreasing of pH and increasing of vitamin C, while the total soluble solid was stable. Total soluble solid increased but vitamin C decreased during storage. Organoleptic test showed that the addition of these antioxidants was basically acceptable.